Oocyte-follicle interactions - Marsh, Adam (2012)
The ovarian follicle is an individual functional unit that provides the optimal environment for the oocyte within to develop. This thesis outlines the research in the field of ovarian follicular dynamics that has already been established, and further develops these findings to explore in greater detail the relationship between the oocyte and its environment, both in an in vitro and in vivo setting, using a variety of species. The first major research area involved studying the role of oocyte-secreted factors, which was examined using a series of dose response experiments. These were performed using an ovine granulosa cell culture model, and elucidated a possible role for a collaborative action of BMP15 and GDF9 in the promotion of oestradiol synthesis, while inhibiting production of progesterone in this species. This finding was then further investigated using an ovine in vivo immune-neutralisation study, the endocrine and histological results of which confirmed these findings in a proportion of these animals, although this study was limited by the animals appearing to have been in seasonal anoestrus.